Overcoming Obstacles in Memorization: Can Goal setting training make Santri Tahfidz Motivated? - Malay, Mohammad Nursalim; Setiawan, Nugroho Arief (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The tahfiz program at Islamic boarding schools is a program specifically for students who want to memorize the Al-Qur’an. However, at Islamic boarding schools students not only study religion but also have to take general lessons. This condition makes students find it difficult to complete their memorization targets, causing a decrease in motivation, dropping out midway and leaving the program. The purpose of this study was to see how much influence goal setting training has on increasing learning motivation in students. The research method used is an experimental research method with the design of one pretest and posttest group. The samples in this study were 90 students from three Islamic boarding schools, namely Nurul Huda Pringsewu Islamic boarding school, YPPTQMH Islamic boarding school and Al-Mujtama Al-Islami Islamic boarding school. The data collection method in this study used a motivational scale totaling 54 items compiled by the researcher. The data analysis technique used is the t-test (paired t-test) with the help of SPSS software. Based on the research results, the value of t = t value = 12.584 with p = 0.000 (p <0.01) means that there is a significant difference in the value of students' learning motivation before the goal setting training and after the goal setting training. The average value of motivation before training was 59.68, increasing to 69.18 after goal setting training.Program tahfiz di Pondok Pesantren merupakan sebuah program yang dikhususkan bagi santri yang ingin menghafal Al-qur’an. Namun, di pondok pesantren santri tidak hanya belajar ilmu agama tetapi juga harus mengikuti pelajaran umum. Kondisi ini membuat santri merasa kesulitan menyelesaikan target hapalanya sehingga menyebabkan turunnya motivasi, putus di tengah jalan dan meninggalkan program tersebut. Tujuan penelitian ini adalah untuk melihat seberapa pengaruh pelatihan goal setting untuk meningkatkan motivasi belajar pada santri. Metode penelitian yang digunakan adalah metode penelitian ekperimen dengan desain satu kelompok pretest dan posttest. Adapun sampel dalam penelitian ini adalah 90 santri dari tiga pondok pesantren, yaitu   pesantren Nurul Huda Pringsewu, Pondon Pesantren YPPTQMH dan Pondok Pesantren Al-Mujtama Al-Islami. Metode pengumpulan data dalam penelitian ini menggunakan skala motivasi berjumlah  54 item yang disusun oleh peneliti. Teknik analisis data yang digunakan adalah uji-t (paired t-test) dengan bantuan software SPSS.  Berdasarkan hasil penelitian diperoleh nilai t = nilai t = 12,584 dengan p = 0.000 ( p < 0.01 ) artinya, terdapat perbedaan signifikan nilai motivasi belajar santri sebelum adanya pelatihan goal setting dengan sesudah pelatihan goal setting. Adapun nilai rata-rata motivasi sebelum pelatihan adalah 59,68 meningkat mejadi  69,18 setelah pelatihan goal setting.